Bifidobacterium-derived short-chain fatty acids and indole compounds attenuate nonalcoholic fatty liver disease by modulating gut-liver axis - Yoon, Sang Jun; Yu, Jeong Seok; Min, Byeong Hyun; Gupta, Haripriya; Won, Sung-Min; Park, Hee Jin; Han, Sang Hak; Kim, Byung-Yong; Kim, Kyung Hwan; Kim, Byoung Kook; Joung, Hyun Chae; Park, Tae-Sik; et al. (Frontiers in Microbiology, 2023)
Emerging evidences about gut-microbial modulation have been accumulated in the treatment of nonalcoholic fatty liver disease (NAFLD). We evaluated the effect of Bifidobacterium breve and Bifidobacterium longum on the NAFLD pathology and explore the molecular mechanisms based on multi-omics approaches. Human stool analysis (healthy subjects [n=25] and NAFLD patients [n=32]) was performed to select NAFLD-associated microbiota. Six-week-old male C57BL/6J mice were fed a normal chow diet (NC), Western diet (WD) and WD with B. breve (BB) or B. longum (BL) (109 CFU/g) for 8 weeks. Liver/body weight ratio, histopathology, serum/tool analysis, 16S rRNA-sequencing, and metabolites were examined and compared. The BB and BL groups showed improved liver histology and function based on liver/body ratios (WD 7.07±0.75, BB 5.27±0.47, and BL 4.86±0.57) and NAFLD activity scores (WD 5.00±0.10, BB 1.89±1.45, and BL 1.90±0.99) (P<0.05). Strain treatment showed ameliorative effects on gut barrier function. Metagenomic analysis showed treatment-specific changes in taxonomic composition. The community was mainly characterized by the significantly higher composition of the Bacteroidetes phylum among the NC and probiotic-feeding groups. Similarly, the gut metabolome was modulated by probiotics treatment. In particular, short-chain fatty acids and tryptophan metabolites were reverted to normal levels by probiotics, whereas bile acids were partially normalized to those of the NC group. The analysis of gene expression related to lipid and glucose metabolism as well as the immune response indicated the coordinative regulation of β-oxidation, lipogenesis, and systemic inflammation by probiotic treatment. BB and BL attenuate NAFLD by improving microbiome-associated factors of the gut-liver axis.